Implementation of Secure Work From Home System Based on Blockchain using NS3 Simulation - Mega Apriani; Diwandaru Rousstia; Fajar Rifai; Ruki Harwahyu; Riri Fitri Sari (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Work from Home (WFH) is an activity carrying out official duties, completing outputs, coordination, meetings, and other tasks from the residence of employees. Implement WFH many users use the zoom application has vulnerabilities. The network architecture used refers to the simple experiment network. In Secure WFH there are 3 offices connected through a router. Each client in each office is connected to the router via a Virtual Private Network (VPN) on a peer-to-peer (P2P). That architecture has 18 nodes that will be simulated. Secure WFH simulation with blockchain combines secure WFH with a bitcoin code simulator from Arthur Gervais's. Implementation of blockchain on secure WFH can increase security but the resulting speed decreases. The decrease in speed when implementing secure WFH is due to the generate block process and the verification process.